Hubungan Frekuensi Harian Mencuci Wajah dan Pemakaian Sabun Wajah Anti Akne Dengan Derajat Keparahan Akne Vulgaris pada Remaja Putri di SMAN 10 Bandar Lampung - Annisa Adietya Pratama; Dwi Indria Anggraini; Syazili Mustofa (Majority, 2021)
Acne vulgaris is a skin problem that often occurs in teenager. Some factors that can cause acne vulgaris include genetic, hormonal, infection, trauma, and diet. The degree of acne is divided into mild, moderate, and severe degrees. Washing face is a prevention or treatment of acne vulgaris, it should be noted the use of the type of face wash and the frequency of facial washing with the incidence of acne vulgaris. Purpose of this research is to find out the relationship of daily frequency facial washing and use of anti acne face wash to the severity of acne vulgaris in teenage girl at SMAN 10 Bandar Lampung. This research used analytic observational method with cross sectional approach. The sample of the research is 89 respondents and using purposive sampling method. The result of univariate analysis was 56,2% of respondents use anti acne face wash and 57,3% of respondents wash their faces ≥ 3 times a day. The result of bivariate analysis showed some variables had a correlation with with the severity of acne vulgaris is the use of anti acne face wash (p value 0,016). Meanwhile, some variables had no correlation with the severity of acne vulgaris witch is the frequency of daily facial washing (p value 0,582). The conclusion is there was relationship between the use of anti acne face wash and the severity of acne vulgaris and there was no relationship between daily frequency facial washing with the severity of acne vulgaris